Evaluasi Kurikulum di MI Riyadul Falah Aikperapa Aikmel Lombok Timur Nusa Tenggara Barat - Wardi, Muhammad Musfiatul; Aqodiah, Aqodiah; Ali, Mustopa (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2023)
This study aims to determine the evaluation of the implementation of the 2013 curriculum at MI Riyadul Palah Aikperapa Aikmel East Lombok and to find out the obstacles to evaluating the implementation of the curriculum at MI Riyadul Falah Aikperapa. The school has been using the 2013 curriculum for a long time. The curriculum is a very important tool in realizing and achieving school education goals. On this basis, this study intends to find evaluations and obstacles to the implementation of the 2013 curriculum at MI Riyadul Palah Aikperapa located in Aimel District, East Lombok Regency, NTB. The focus of this journal issue is how to evaluate the implementation of the curriculum and the obstacles encountered in evaluating the implementation of the curriculum. In this assessment the author uses a qualitative descriptive research type. with three stages of data collection namely, (1) observation (observation), (2) interview (interview), and (3) documentation. The research data collection method uses non-statistical analysis suitable for descriptive data or structural data that is not realized in the form of numbers, all data is analyzed using identification, classification, and interpretation. The results obtained are (1) One of the evaluations of the implementation of the 2013 curriculum related to teacher readiness in planning, implementation and assessment has been carried out properly. (2) the obstacles encountered are: Teachers still do not understand the assessment in the 2013 curriculum in recapitulating assessments on report cards, preparing lesson plans and the learning process.